1996
DOI: 10.1016/0014-5793(95)01438-1
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activity of the ribosome‐bound nascent polypeptide

Abstract: tide extended by 1 to 59 amino acid residues at the C-terminus and still attached to the ribosome. The ribosomes bearing those elongated luciferases were isolated and the enzyme activity assay revealed that the nascent luciferase was enzymatically active if the C-terminus has been extended by 26, 27, 31, 42 and 59 extra amino acid residues. Extensions by 1, 12 or 21 residues were not enough for the ribosome-bound nascent enzyme to attain its active conformation.These results were first reported at the conferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
54
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 23 publications
4
54
0
1
Order By: Relevance
“…This underscores the high degree of flexibility in the naagainst antibodies to each of the 21 30S proteins by the method scent peptide which, as noted above, is consistent with the conof Gulle et al [25]. The results confirmed the preliminary analy-cept of co-translational folding [5,6]. Co-translational folding sis and showed that the proteins involved were S1, S2, S4 and, also implies that the ribosomal tunnel must be wide enough to to a lesser extent, S3.…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…This underscores the high degree of flexibility in the naagainst antibodies to each of the 21 30S proteins by the method scent peptide which, as noted above, is consistent with the conof Gulle et al [25]. The results confirmed the preliminary analy-cept of co-translational folding [5,6]. Co-translational folding sis and showed that the proteins involved were S1, S2, S4 and, also implies that the ribosomal tunnel must be wide enough to to a lesser extent, S3.…”
Section: Methodssupporting
confidence: 87%
“…In our own experiments in this area, we have attempted peptides) were considered in the cross-link analyses. Thus, the to define the path followed by the nascent peptide through the nascent peptide is clearly very flexible within the ribosomal tunnel, a property which would be expected if co-translational foldCorrespondence to R. Brimacombe, Max-Planck-Institut für Mole-ing [5,6] is to occur, since the peptide must be able to continu- …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo, folding of nascent proteins proceeds cotranslationally (10,11) and is influenced by the rate of ribosome transit through the mRNA template. What distinguishes synonymous codons that encode a given degenerate amino acid is the abundance of their corresponding tRNA, which is lower for infrequently used codons than for frequently used codons (12,13).…”
mentioning
confidence: 99%